The Influence of Personality and Social Support on Adolescent Sports Motivation - Fanisa Nurul Widhi; Yudha Munajat Saputra; Nurlan Kusmaedi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study's aim was to investigate the factors social support and personality contribute to the motivation of adolescent sportsmen. The research method used is quantitative, with descriptive correlative type. Subject of the study is 121 students of Junior high school 1 Lengkong, Sukabumi Regency. The measurements were composed of the Dark Triad Dirty Dozen (DTDD) for personality, the Multidimensional Scale of Perceived Social Support (MSPSS) for social support, and the Behavioral Regulation in Exercise Questionnaire (BREQ-3) for exercise motivation. Data were analyzed using the Spearman and multiple linear regression analysis. It was found that social support and personality significantly contribute to the exercise motivation (t = 7.667; p = 0.000 and, t = 2.512; p = 0.013 respectively) and concurrently both play meaningful roles on the exercise motivation (F = 31.454; p = 0.000). The value of R² is 0.348; that is,34.8% of variation between adolescents' sports motivation was explained by the personality and social support variables, while the other remaining 65.2% could be attributed to other factors. Thus it can also be suggested that in enhancing sports motivation during adolescence, social support is more important than personality.